Trap [videorecording (Blu-Ray)] - Shyamalan, M. Night; Hartnett, Josh, 1978-; Donoghue, Ariel; Shyamalan, Saleka Night; Shyamalan, Saleka Night; Mills, Hayley; Pill, Alison, 1985-; Mukdeeprom, Sayombhu; Herdís Stéfansdóttir (Warner Bros. Entertainment Inc., 2024)
A father and teen daughter attend a pop concert, where they realize they're at the center of a dark and sinister event.